Toxic Metal Ions Removal from Electroplating Wastewater Using Polymer Chelating - Md Lutfor Rahman; Mohd Sani Sarjadi; Sazmal E. Arshad; Baba Musta; Mohd Harun Abdullah; Shaheen M. Sarkar; Emmet J. O'Reilly (2020)
Background: Empty fruit bunch (EFB) is a type of biomass waste product formed during the production process of palm oil. In the present work, EFB was used to prepare a cellulose-graftcopolymer which can be converted into poly(amidoxime)-poly(hydroxamic acid) ligands suitable for the removal of heavy metals from electroplating wastewater. Methods and Results: Poly(amidoxime)-poly(hydroxamic acid) ligands were synthesized from the poly(acrylonitrile-co-methyl acrylate) grafted palm cellulose and were analyzed via FT-IR and FESEM. The binding capacity (qe) with the metals ions such as copper (Cu2+), iron (Fe3+), cobalt (Co2+), nickel (Ni2+) and lead (Pb2+) were 341, 290, 284, 204 and 482 mg g-1, respectively at pH 6. The pseudo-first-order kinetic model is fitted with the results confirming heavy metal adsorption. The isotherm study was conducted using a linear plot of the Langmuir isotherm where results were significantly different from the experimental value (maximum adsorption, qe), indicating that adsorption does not occur on a single layer. However, the coefficient of the correlation values obtained using the Freundlich isotherm model were acceptable (R2>0.99), and it was concluded that adsorption was multilayered with some metal ions. Conclusion: The polymeric ligands synthesized here showed excellent adsorption of heavy metals from electroplating wastewater containing a notable amount of copper and iron metal ions.